RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE IN STUDENTS’ ACADEMIC ACHIEVEMENT - Moh. Firmansyah; Abd Rohman (Jurnal Madako Education, 2020)
The current research is entitled Relationship between Emotional Intelligence, Spiritual Intelligence in Students’ Academic Achievement. The objective of this research which were: 1) is there any significant correlations between Spiritual Intelligence and Emotional Intelligence simultaneously students in academic achievement. 2) Which one the aspects that influence spiritual intelligence and emotional Intelligence in academic achievement. This sample was taken simple purposive sampling. Instruments of this study used questionnaires and documentation. This study used a quantitative descriptive method. To know the answer hypothesis the researcher used analysis of multiple correlations. Based on the analysis quantitative descriptive showed that sig F change = 0.177, it means that the correlation between emotional intelligence and spiritual intelligence with simultaneously to the students' academic achievement is negligible refers to the table interpretation by Sugiyono (2012) who stated that the coefficient interval between 0,00-0,199 the qualification is negligible. The result of the formula about the significant multiple correlations between emotional and spiritual intelligence in students' academic achievement is = 1.8701652319935. Because the total significance is = 1.8701652319935 > 0,05, it concludes if there was no significant correlation between emotional and spiritual intelligence in students' academic achievement.Keywords: Correlation, Emotional Intelligence, Spiritual Intelligence.